2015
DOI: 10.1002/term.2056
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up after advanced core decompression

Abstract: The so-called "Advanced Core Decompression" (ACD) is a new option that tries to remove the necrotic tissue in patients with osteonecrosis of the femoral head (AVN) in a minimally invasive way by the use of a percutaneous expandable reamer and refilling with a resorbable and osteoinductive bone-graft substitute. Seventy-two hips of sixty patients with a mean follow-up of 29.14 months after ACD have been included in this study. Patients underwent physical examination preoperatively and six weeks after surgery as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…It also classifies femoral head necrosis according to its corresponding acetabulum weight-bearing area as A, B, C1, and C2 types. Classen et al [ 21 ] adapted advanced core decompression surgery to treat osteonecrosis of the femoral head, and they reported that defect type C had a significantly higher rate of femoral head collapse than the smaller defects sizes A and B. Lieberman et al [ 8 ] systematically reviewed 5 reports on the correlation between necrosis location and clinical failure rates. The results suggest that when the femoral head necrotic area did not exceed the corresponding inner weight-bearing area by 30%, only one out of 22 cases (4.5%) was a clinical failure, while when the femoral head necrosis area exceeded the corresponding inner weight-bearing area by 60%, 41 out of 91 cases (45%) were clinical failures.…”
Section: Discussionmentioning
confidence: 99%
“…It also classifies femoral head necrosis according to its corresponding acetabulum weight-bearing area as A, B, C1, and C2 types. Classen et al [ 21 ] adapted advanced core decompression surgery to treat osteonecrosis of the femoral head, and they reported that defect type C had a significantly higher rate of femoral head collapse than the smaller defects sizes A and B. Lieberman et al [ 8 ] systematically reviewed 5 reports on the correlation between necrosis location and clinical failure rates. The results suggest that when the femoral head necrotic area did not exceed the corresponding inner weight-bearing area by 30%, only one out of 22 cases (4.5%) was a clinical failure, while when the femoral head necrosis area exceeded the corresponding inner weight-bearing area by 60%, 41 out of 91 cases (45%) were clinical failures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effect of certain parameters on the long-term outcome of ONFH therapy. These known parameters include lesion stage and lesion size as well as the presence of risk factors and concomitant hip pathologies [3,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary endpoint was set as the evidence of age-or sex-dependent differences in joint As it is known that the treatment outcome of ONFH depends on several co-factors, the subgroups were further analysed regarding the presence and distribution of possible confounders. The parameters recorded in this context include the size of the necrotic lesion (A-C according the ARCO and Steinberg classifications), the presence of risk factors (immunosuppressive therapy, high-dose corticosteroid treatment, abuse of alcohol and nicotine and coagulation disorders) and radiological evidence of cam-type deformity of the affected hip using the alpha angle according to Nötzli [21,22,28,29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we know that the success of ONFH therapy depends to a large extent on the stage of the disease and the size of the lesions. Stages beyond ARCO 2 and Steinberg 2, as well as Type C lesions, clearly show a worse outcome regardless of the type of therapy performed (Classen, Warwas, Jäger, & Landgraeber, ; Mont, Jones, & Hungerford, ). The present study indicates that the alpha angle and the head–neck offset are possible (co)factors that influence therapy outcome in ONFH patients.…”
Section: Discussionmentioning
confidence: 99%